Optimized cloud resource management and scheduling : theories and practice - Tian, Wenhong (Morgan Kaufmann, 2015)
This book identifies research directions and technologies that will facilitate efficient management and scheduling of computing resources in cloud data centers supporting scientific, industrial, business, and consumer applications. It serves as a valuable reference for systems architects, practitioners, developers, researchers and graduate level students. It explains how to optimally model and schedule computing resources in cloud computing; provides in depth quality analysis of different load-balance and energy-efficient scheduling algorithms for cloud data centers and Hadoop clusters; introduces real-world applications, including business, scientific and related case studies; discusses different cloud platforms with real test-bed and simulation tools. --